Strategies for translating the Ihtebak in the Qur’an (Makarem Al-Shirazi’s translation of Surat Al-Imran into Persian as a model) - Maryam Khani; Habib Keshavarz; sayyed reza Mirahmadi (دراسات فی اللغه العربیه و آدابها)
Translation of Alihtebak in the Noble Qur’an (Makarim Al-Shirazi’s translation of Surat Al-Imran into Persian as an example). To translate the Holy Qur'an, its paramount importance, a large number of translators in Iran translated it into Persian. And according to the sensitivity of translating holy books, including the Qur’an, we see strenuous efforts to transfer it from its original language in terms of content and language in the best way.Whoever plays this sensitive role faces many challenges in translating the meanings of the Qur’an, in addition to what is related to the use of literary arts. Alehtebak is a wonderful art frequently that has been used in the Qur’an a lot, and translators have difficulty in transmitting verses in which this art was used.This article, with a descriptive and analytical approach, aimed to shed light on the art of Alehtebak in Surat Imran and then study Makarim Shirazi’s translation for the verses in which alehtebak was used. Results point out that the translator doesn't care about this art in translating.